INTELLECTUAL PROPERTY LAW IN THE DIGITAL AGE: CHALLENGES AND OPPORTUNITIES FOR VISUAL AND PERFORMING ARTISTS - Mehpara; Nilakshi; Trivedi, Vivek; Waseem; Sharma, Anupam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines how intellectual property (IP) law is evolving in relation to visual and performing arts in our digital era, with a focus on the Indian context. By analyzing recent court cases, laws, and industry practices, it explores the key challenges artists face in protecting and monetizing their work online, as well as new opportunities created by digital technologies. The research finds that while digital reproduction and distribution have made copyright enforcement much harder, they have also opened up exciting new avenues for creation, collaboration, and connecting with audiences. The paper argues that IP frameworks need to be updated to better balance protecting artists’ rights with the realities and possibilities of our digital world, particularly in the Indian legal and cultural landscape.